The Dhatu on fields of Meditation and Practices - Yu, Le Cai (BUDDHO, 2025)
The concept of Dhātu (Pāli: धातु), commonly translated as “element” or “constituent,” occupies a central position in early Buddhist philosophical analysis and meditative praxis. This study aims (1) to examine the conceptual foundations of Dhātu as presented in early Buddhist canonical and commentarial texts, particularly in relation to meditation and insight practice; (2) to analyze the role of the Four Great Elements (Mahābhūta earth, water, fire, and air) in meditative contemplation and their function in cultivating direct understanding of impermanence (anicca), suffering (dukkha), and non-self (anattā); and (3) to critically assess the extent to which Dhātu theory is integrated into modern meditation practices, especially contemporary mindfulness-based approaches. Employing a qualitative documentary research methodology, the study systematically analyzes primary sources from the Pāli Canon, including the Nikāyas and Abhidhamma, alongside key commentarial texts such as the Visuddhimagga. Secondary sources include modern scholarly interpretations and contemporary meditation manuals. Textual analysis and thematic comparison are used as the primary research tools to trace doctrinal continuity, interpretive developments, and practical applications of Dhātu contemplation across historical and modern contexts. The findings indicate that, in early Buddhism, Dhātu functions as both an analytical framework and a practical meditative method aimed at deconstructing the notion of a permanent self through direct experiential insight. However, modern mindfulness-based practices tend to marginalize elemental analysis, favoring generalized attentional techniques. This study concludes that the diminished emphasis on Dhātu represents a significant doctrinal and practical gap. By highlighting its meditative efficacy and philosophical depth, the research argues for the reintegration of Dhātu-based contemplation into contemporary meditation frameworks, thereby enriching both theoretical understanding and experiential insight within modern Buddhist practice.